2013
DOI: 10.1371/journal.pone.0062921
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of p38 MAPK Inhibition Combined with G-CSF Administration on the Hematoimmune System in Mice with Irradiation Injury

Abstract: The acute and residual (or long-term) bone marrow (BM) injury induced by ionizing radiation (IR) is a major clinic concern for patients receiving conventional radiotherapy and victims accidentally exposed to a moderate-to-high dose of IR. In this study, we investigated the effects of the treatment with the p38 inhibitor SB203580 (SB) and/or granulocyte colony-stimulating factor (G-CSF) on the hematoimmune damage induced by IR in a mouse model. Specifically, C57BL/6 mice were exposed to a sublethal dose (6 Gy) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…1 a. Peripheral blood was obtained via the orbital sinus 1 month after 4 Gy TBI, and WBCs, platelets, and hematocrit were measured as described previously [ 25 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 a. Peripheral blood was obtained via the orbital sinus 1 month after 4 Gy TBI, and WBCs, platelets, and hematocrit were measured as described previously [ 25 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty four male mice were divided into four groups randomly: (a) control group; (b) 4 Gy group; (c) G-CSF group; (d) G-CSF + 4 Gy group. Mice from G-CSF + 4 Gy group and 4 Gy group were exposure to 4 Gy γ-rays (dose rate:1.08 Gy per minute) using an Exposure Instrument Cammacell-40 (Atomic Energy of Canada Lim), and then administered with G-CSF or vehicle (saline in 100 ul volume) twice a day for 7 days with intraperitoneal injections at an dose of 1 μg/mouse [ 25 , 39 ]. The mice from G-CSF group and control group were not exposure to irradiation, and were treated in a manner similar to that described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we first confirmed that MLA could increase the survival rate of mice exposed to 7.2 Gy total body irradiation (TBI). Second, we examined the protective effects of MLA on the hematopoietic system in mice exposed to 6 Gy TBI, which could result in virtually no lethality for up to 30 days post-irradiation [ 14 ]. Finally, we investigated the mechanism by which MLA provides protection against IR injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that exposure to sub-lethal doses of 137 Cs γ ray TBI led to long-term BM suppression and induced a decrease in the peripheral blood cell counts [ 14 , 15 ]. To investigate the SB203580 treatment effects on IR-induced hematopoietic system injury, the numbers of peripheral blood cells were analyzed 80 days after 6 Gy TBI.…”
Section: Resultsmentioning
confidence: 99%